Kinetic friction of boardercross-snowboards - Hasler, M.; Schindelwig, K.; Knoflach, C.; Reichl, W.; Nachbauer, W. (Procedia Engineering, 2014)
The purpose of this study was to analyze the kinetic friction of different combinations of snowboard base structures and waxes. On a linear tribometer in a cold lab 3 snowboards with 3 different base structures were first waxed with a training wax. Then the friction coefficient was assessed at 2 m/s, 5 m/s and 8 m/s. Subsequently the boards were prepared with a racing finish and the friction coefficient of the boards was measured again.